Massive Urinary Protein Excretion Associated with Greater Neonatal Risk in Preeclampsia - Mateus, Julio; Newman, Roger; Sibai, Baha M.; Li, Qing; Barton, John R.; Combs, C. Andrew; Guzman, Edwin; Boggess, Kim A.; Gyamfi, Cynthia; von Dadelszen, Peter; Woelkers, Doug (American Journal of Perinatology Reports, 2017)
Objective The objective of this study was to compare clinical outcomes of preeclamptic pregnancies according to the proteinuria level.Study Design Secondary analysis of a multicenter prospective cohort study of women with preeclampsia (PE) symptomatology. Nonproteinuria, mild-proteinuria, and massive-proteinuria PEs were defined as: < 165 mg in 12 hours or < 300 mg in 24 hours, 165 mg to 2.69 g in 12 hours or 300 mg to 4.99 g in 24 hours, and ≥ 2.7 g in 12 hours or ≥ 5.0 g in 24 hours, respectively. Individual and composite maternal, fetal, and neonatal outcomes were compared among the PE groups.Results Of the 406 analyzed pregnancies, 36 (8.8%) had massive-proteinuria PE, 268 (66.0%) mild-proteinuria PE, and 102 (25.1%) nonproteinuria PE. Compared with the other groups, massive-proteinuria PE women had significantly higher blood pressures (p < 0.001), epigastric pain (p = 0.007), and uric acid serum levels (p < 0.001) prior to delivery. Composite maternal morbidity was similar across the groups. Delivery < 340/7 weeks occurred in 80.6, 49.3, and 22.5% of massive-proteinuria, mild-proteinuria, and nonproteinuria PE groups, respectively (p < 0.0001). Composite adverse neonatal outcomes were significantly higher in the massive-proteinuria PE compared with the other groups (p = 0.001).Conclusion While potentially not important diagnostically, massive proteinuria is associated with more severe clinical manifestations of PE prompting earlier delivery.
Keywords: proteinuria; PETRA study; preeclampsia; complications; preterm delivery